2004
DOI: 10.1161/01.res.0000133677.77465.38
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Fluid Shear Response in Leukocytes to Hemodynamic Resistance in the Spontaneously Hypertensive Rat

Abstract: Abstract-The mechanisms for elevation of peripheral vascular resistance in spontaneously hypertensive rats (SHR), a glucocorticoid-dependent form of hypertension, are unresolved. An increase in hemodynamic resistance caused by circulating blood may be a factor. Physiological fluid shear stress induces a variety of responses in circulating leukocytes, including pseudopod retraction. Due to high rigidity, leukocytes with pseudopods have greater difficulty to pass through capillaries. Because SHR have more circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 38 publications
0
68
1
Order By: Relevance
“…In the spontaneously hypertensive rat (SHR), which represents a model of hypertension with a genetic background, the microcirculation is characterized by smooth muscle medial hyperplasia, smooth muscle hypertrophy, enhanced smooth muscle longitudinal coverage, enhanced microvessel specific oxidative stress, elevated counts of activated circulating leukocytes, enhanced capillary flow resistance, impairment of selectin-mediated leukocyte adhesion, and extensive non-uniform endothelial cell apoptosis (Suematsu et al, 2002;Fukuda et al, 2004). These characteristics represent a complex remodeling scenario across multiple scales.…”
Section: Introductionmentioning
confidence: 99%
“…In the spontaneously hypertensive rat (SHR), which represents a model of hypertension with a genetic background, the microcirculation is characterized by smooth muscle medial hyperplasia, smooth muscle hypertrophy, enhanced smooth muscle longitudinal coverage, enhanced microvessel specific oxidative stress, elevated counts of activated circulating leukocytes, enhanced capillary flow resistance, impairment of selectin-mediated leukocyte adhesion, and extensive non-uniform endothelial cell apoptosis (Suematsu et al, 2002;Fukuda et al, 2004). These characteristics represent a complex remodeling scenario across multiple scales.…”
Section: Introductionmentioning
confidence: 99%
“…What may change and contribute to "abnormal" behavior is their sensitivity to the surrounding fluid flow mechanoenvironment with a negative impact on the ability of fluid shear stress to deactivate the neutrophils. Along this line, the work of Geert SchmidSchönbein at the University of California, San Diego has demonstrated that attenuated neutrophil shear responses contribute to the microvascular pathobiology observed in spontaneously hypertensive rats (SHRs) [110] and, in doing so, illustrated the potential impact of impaired shear stress mechanotransduction on cardiovascular health.…”
Section: Neutrophil Mechanosensitivity and Cardiovascular Diseasementioning
confidence: 99%
“…Although the increased activity of neutrophils is not associated with increased adhesion to microvascular endothelium [78], their increased numbers raise peripheral vascular resistance [110]. One possible explanation is that circulating activated neutrophils in SHRs release vasoactive substances that constrict the small arteries and arterioles; this has been documented for atherosclerosis [114][115][116].…”
Section: Impaired Fluid Shear Responses and Downstream Effects On Vasmentioning
confidence: 99%
See 2 more Smart Citations